(Re)defining Esotericism Fluid Definitions, Property Clusters and the Cross-Cultural Debate - Engler, Steven; Gardiner, Mark Q. (Aries - Journal for the Study of Western Esotericism, 2024)
This article moves past discussing definitions of esotericism to clarifying the nature of definition itself. After reviewing different approaches to definition, we argue that rigid definitions (which propose necessary and sufficient conditions) are problematic, and that fluid definitions (which seek to clarify, explain, teach etc.) are a better alternative. We then discuss homeostatic property cluster definitions, which are like family-resemblance definitions, but with explicit justification for the particular set of defining criteria. We propose a related but more flexible stable property cluster definition of esotericism. It is intended as a useful focus for ongoing discussion, not as a candidate for the single correct definition. Throughout the article, we contrast meaning realism and meaning antirealism (not ontological realism/antirealism), making a case that the latter is more useful in this context. We end by suggesting that our definitional approach has value for exploring both the global spread of western esotericisms and, more importantly, the extent to which esotericism intersects with the semantic fields of comparable categories in other languages and cultures.
Created from Fastlane, Scopus look-up
Keywords: definition; esotericism; homeostatic property cluster definition; polythetic definition; religion; semantic theory